2020
DOI: 10.3390/ijms21176161
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Disturbs Gut–Blood Barrier and Increases Plasma Trimethylamine, a Toxic Bacterial Metabolite

Abstract: Trimethylamine (TMA) is a gut bacteria product oxidized by the liver to trimethylamine-N-oxide (TMAO). Clinical evidence suggests that cardiovascular disease is associated with increased plasma TMAO. However, little headway has been made in understanding this relationship on a mechanistic and molecular level. We investigated the mechanisms affecting plasma levels of TMAO in Spontaneously Hypertensive Heart Failure (SHHF) rats. Healthy Wistar Kyoto (WKY) and SHHF rats underwent metabolic, hemodynamic, histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
1
19
0
3
Order By: Relevance
“…A previous experiment with rats suggested that heart failure might be associated with functional and structural alterations in intestinal integrity, leading to increased gut-to-blood penetration of TMA and a subsequent elevation in serum TMAO levels (Drapala et al, 2020 ). In contrast to heart failure, acute coronary syndrome, which includes AMI, is an acute cardiological disease and a severe medical emergency associated with a sudden reduction in blood flow to the heart.…”
Section: Introductionmentioning
confidence: 99%
“…A previous experiment with rats suggested that heart failure might be associated with functional and structural alterations in intestinal integrity, leading to increased gut-to-blood penetration of TMA and a subsequent elevation in serum TMAO levels (Drapala et al, 2020 ). In contrast to heart failure, acute coronary syndrome, which includes AMI, is an acute cardiological disease and a severe medical emergency associated with a sudden reduction in blood flow to the heart.…”
Section: Introductionmentioning
confidence: 99%
“…However, the change in intestinal barrier function may be underappreciated. Recently, Drapala et al (2020) reported that rats with HF caused by spontaneous hypertension exhibited intestinal barrier dysfunction and increased intestinal permeability, which could drive intestinal microbiota translocation into systemic circulation, further activate the systemic immune response and exacerbate damage to other organs (Chen et al, 2019). In particular, the intestinal flora metabolite lipopolysaccharide (LPS) is closely associated with a variety of CNS diseases (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, at present, more and more studies have found that TMAO is inextricably linked to hypertension, 9 chronic obstructive pulmonary disease, 19 heart failure, 11,17,20 obesity, 21 metabolic dysfunction, 22 atherosclerosis and coronary heart diseases, 9,10,23 which are known as the common risk factors for AF and motivates a renewed interest in examining the relation between TMAO and AF. However, these results have not been confirmed in AF models and prospective clinical studies, and the degree and mechanism of modifying these risk factors on AF by regulating intestinal microbes and their metabolites such as TMAO are still needed to be explored.…”
Section: Tmao and Risk Factors Of Afmentioning
confidence: 99%